A robótica educacional no ensino-aprendizagem da matemática na educação básica: metassíntese qualitativa de pesquisas brasileiras entre 2007 e 2017 - Braz, Jussara Elizandra (2019)
We know that the use of digital technologies is increasingly accessible, that students have access to various resources and that they often do not use them properly. The school as a training agent tries to accompany and insert in its context technological resources with the intention of involving the students and taking advantage of wh at the technologies have to offer. One of the resources that advances into the classroom is Educational Robotics which has PAPERT (1960) as its precursor. He saw the computer as an attraction for children and could be used as a resource to facilitate the learning process, so using the LOGO language began a work with pedagogic strategies that enchanted several generations. In this sense, the present dissertation aims to search the possible contributions of Educational Robotics as a teaching-learning tool of mathematics in the scope of Brazilian basic education. For this purpose, the qualitative meta-synthesis of the researches carried out in Brazil between 2007 and 2017 was developed. The search for mapping was carried out in dissertations and theses located in the databases of CAPES, BDTD (Digital Library of Theses and Dissertations) and in Virtual Libraries. The results were submitted to qualitative metassynthesis and later triangulated with the theoretical contribution. We realized that the RE is a potential tool as a support in the teaching of Mathematics, taking into account the competences listed by BNCC. For better results it is imperative that the RE is included in the Curriculum of Education and meets all the series of teaching, its potential is through continuous action and not in isolated projects.